2022
DOI: 10.3390/cancers14041000
|View full text |Cite
|
Sign up to set email alerts
|

Upper Gastrointestinal Cancer Surveillance in Lynch Syndrome

Abstract: Lynch syndrome is a common hereditary cancer predisposition syndrome associated with increased digestive cancer risk including colorectal, gastric, and duodenal cancers. While colorectal cancer surveillance is widely accepted to be an important part of a comprehensive Lynch syndrome risk management plan, the use of upper gastrointestinal cancer surveillance in Lynch syndrome remains more controversial. Currently, upper gastrointestinal cancer surveillance guidelines for Lynch syndrome vary widely, and there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 73 publications
(129 reference statements)
0
9
0
Order By: Relevance
“…LS due to a PV in MLH1 , MSH2 , MSH6 , PMS2 , or EPCAM is one of the most common gastric cancer predisposition syndromes, affecting 1 in 279 individuals 145 . Gastric cancer risk in LS can be up to 9 per cent, however, but varies by genotype, with PMS2 variants associated with lower gastric cancer risk than other variants 125 . Male sex, having an FDR with gastric cancer, and older age are also associated with a higher risk of gastric cancer in LS 146 .…”
Section: Hereditary Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…LS due to a PV in MLH1 , MSH2 , MSH6 , PMS2 , or EPCAM is one of the most common gastric cancer predisposition syndromes, affecting 1 in 279 individuals 145 . Gastric cancer risk in LS can be up to 9 per cent, however, but varies by genotype, with PMS2 variants associated with lower gastric cancer risk than other variants 125 . Male sex, having an FDR with gastric cancer, and older age are also associated with a higher risk of gastric cancer in LS 146 .…”
Section: Hereditary Gastric Cancermentioning
confidence: 99%
“…Studies of gastric surveillance in LS from the USA 147–149 and Europe 125 , 150 have illustrated that surveillance leads to clinically actionable findings as well as early-stage gastric cancers. A recent meta-analysis of upper gastrointestinal surveillance demonstrated that the pooled event rate for detecting an upper gastrointestinal cancer was 0.9 per cent, a high-risk lesion was 4.2 per cent, and an actionable finding was 6.2 per cent 151 .…”
Section: Hereditary Gastric Cancermentioning
confidence: 99%
“…Multiple professional societies have developed guidelines addressing management of gastric cancer risk in Lynch syndrome. 35,[41][42][43][44][45][46][47][48] However, significant heterogeneity exists at present between these guidelines regarding whether gastric surveillance should be performed, the age of initiation, and recommended interval for upper GI surveillance in Lynch syndrome, which has been well-summarized in a recent review by Kumar et al 49 In part, the variability of different guidelines has resulted from limited data demonstrating clinical effectiveness of gastric cancer surveillance in Lynch Cancer Management and Research 2022:14 https://doi.org/10.2147/CMAR.S277898 DovePress 2957 syndrome, as well as uncertainty regarding which high-risk individuals are most in need of surveillance. Fortunately, this is an area of ongoing active research, with recent studies of upper endoscopic surveillance in Lynch syndrome supporting surveillance as effective at detecting pre-cancerous lesions and early-stage gastric cancers.…”
Section: Surveillancementioning
confidence: 99%
“…It is the authors’ practice that all individuals with Lynch syndrome, regardless of the causative gene, initiate surveillance upper endoscopy at age 30 (or 2–5 years before the youngest age of diagnosis if there is a family history of gastric cancer under age 35), repeating every 2–3 years with consideration of shorter intervals with a family history of upper GI cancer or in the presence of precancerous lesions (incomplete or extensive gastric intestinal metaplasia, gastric/duodenal adenoma or Barrett’s esophagus with dysplasia). 49 NCCN recently adopted a similar approach by recommending upper GI surveillance starting between ages 30–40 and repeating every 2–4 years for all MLH1, MSH2/EPCAM , and MSH6 PV carriers with consideration of upper GI surveillance in PMS2 PV carriers. 35 Surveillance should also be performed with use of high definition, white light endoscopy, ideally performed at the time of surveillance colonoscopy, with inclusion of random biopsies of the proximal and distal stomach to evaluate for Helicobacter pylori , intestinal metaplasia and autoimmune gastritis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation